The Impact of Human Capital and Women’s Participation on Poverty in Indonesia - Ericha Ramadhani; Muhammad Anas (Universitas KH. Abdul Chalim Mojokerto, 2026)
Poverty is an important indicator in assessing the level of public welfare and the success of a country's economic development. This study aims to estimate the effect of female workers, females' years of schooling, females' life expectancy, and females' productivity on the poverty rate in 34 provinces in Indonesia from 2018 to 2024 using a panel data regression model with a Fixed Effects Model (FEM) approach. The regression results indicate that females' mean years of schooling negatively impact the poverty rate, while the number of female workers and female workers' productivity positively impact poverty rate. Meanwhile, females' life expectancy is found to have no effect on poverty rate. Therefore, the government is expected to formulate policies that focus on improving the quality and empowerment of the female workforce through the transformation of the informal sector to the formal sector, expanding access to higher education, implementing gender-neutral job evaluations, and providing gender-friendly facilities such as daycare centers so that increased women's workforce participation and productivity can be balanced with a reduction in poverty rates.